International trade law - Ahmad, Muhamad Hassan; Ali Mohamed, Ashgar Ali; Masum, Ahmad; Arowosaiye, Yusuf Ibrahim; Eishan Jan, Mohammad Naqib; Lilienthal, Gary (LexisNexis Malaysia Sdn Bhd, 2025)
International trade environment is heavily regulated by various laws at both international and domestic level. Thus, it is essential to be familiar with the legal implications for commercial transactions carried out among people doing businesses from different jurisdictions. Basically, an international sale involves a transaction between a buyer with the place of business in one country and a seller from another. Furthermore, it requires the carriage of goods from the seller’s country to the buyer’s country, usually by sea, air or land. Hence, for an international sale to be completed, a number of other transactions are also necessary to be carried out among various parties from different jurisdictions such as contract of carriage, contract of insurance, and contract for payment, among others.